The time is out of joint: temporal disorders in the late modern condition - Moser, Walter (Revista de Letras, 2007)
It is my contention here that the complex temporal order, or this manifold way in which very different areas of practire can be interrelated by their common participation in the same temporal order – which I will reduce to the formula “progressive literarity” – today is “out of joing”. My main task here consists in an inventory of some of these “temporal discorders” in order to create the possibility of evaluating pertaining to the same configuration of temporal change. According to my hypothesis, these disorders constute symptoms – and in their coincidence a syndrome – of the crisis of modernity. They are part of the late modern condition , which is also ours. According to this point of view, modern manipulation and control of time loses ground, wealens in terms of functonam efficiency, raises cognitive doubts. It’s precisely through its cracks that we regain the freedon not only to see, but also to accept the multilayered complexity of our temporal experience.